Koinfeksi Coronavirus dan Demam Berdarah Dengue : Literatur Review - Faizatunnisa Zamzam (Jurnal Medika Hutama, 2022)
Covid-19 infection and dengue hemorrhagic fever share clinical features that are sometimes difficult to distinguish. During the Covid-19 pandemic, prevention and reduction of Covid-19 cases are prioritized so that problems with other infectious diseases such as dengue hemorrhagic fever are neglected. It is not uncommon for misdiagnosis to occur and it is unavoidable, especially in tropical countries with many other infectious diseases. This study conducted a literature review to view and review the results of studies that have been carried out related to Coronavirus and Dengue Hemorrhagic Fever from various countries. The study in this study aims to determine the coinfection of dengue hemorrhagic fever with covid-19 and to find out whether the two diseases can be distinguished during the ongoing covid-19 pandemic. The Scopus e-database search in this study resulted in 183 articles with 153 open access articles, of the total e-databases, only 5 articles were reviewed. Of the 5 articles reviewed, there were 3 case report studies, 1 prospective cohort study (group description), and 1 cross-sectional study. Of the five research subjects, patients came with the same symptoms, namely patients with fever, myalgia, sore throat, vomiting, and diarrhea, on average, patients only checked for pain after 5-7 days from the onset of symptoms. Co-infection of dengue and covid-19 in outbreak areas must be watched out for because they have the same clinical symptoms and laboratory findings. So it is important to consider during this pandemic, infectious diseases such as dengue hemorrhagic fever cannot be underestimated, especially in tropical and subtropical countries that are prone to endemic infectious diseases.